Hands-On Spring Security 5 for Reactive Applications : Learn Effective Ways to Secure Your Applications with Spring and Spring WebFlux. - John, Tomcy (Packt Publishing Ltd, 2018)
Security is one of the most vital concerns for any organization. The complexity of an application is compounded when you need to integrate security with existing code, new technology, and other frameworks. This book will show you how to effectively write Java code that is robust and easy to maintain.